Composing cyberspace : - Holeton, Richard (McGraw-Hill, 1998)
This innovative reader addresses the social, cultural, political, and educational implications of today's burgeoning information and communication technologies in substantial critical depth. Using three broad human themes--Constructing Identity, Building Community, and Seeking Knowledge--this brief freshman reader engages students in exciting rhetorical issues, including "Gender Online," "The Global Village," and "Information Overload and New Media." In each case, hopeful and optimistic views are balanced with incisive technology criticism, helping to make cutting-edge social issues intellectually coherent and accessible to your students.